2019
DOI: 10.1002/hep.30366
|View full text |Cite
|
Sign up to set email alerts
|

Vessels That Encapsulate Tumor Clusters (VETC) Pattern Is a Predictor of Sorafenib Benefit in Patients with Hepatocellular Carcinoma

Abstract: Sorafenib is the most recommended first‐line systemic therapy for advanced hepatocellular carcinoma (HCC). Yet there is no clinically applied biomarker for predicting sorafenib response. We have demonstrated that a vascular pattern, named VETC (Vessels that Encapsulate Tumor Clusters), facilitates the release of whole tumor clusters into the bloodstream; VETC‐mediated metastasis relies on vascular pattern, but not on migration and invasion of cancer cells. In this study, we aimed to explore whether vascular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 29 publications
8
80
2
Order By: Relevance
“…This vascular phenotype can be detected with increasing frequency, from the earliest stages of HCC, and its assessment is easy and reliably reproducible even in small‐sized tissues such as liver biopsy. In advanced HCC, VETC has been recently suggested to act as a predictor of sorafenib benefit; however, our data support the assessment of the VETC phenotype also in nonadvanced and resectable HCC for the identification of HCC patients at high risk of a more rapid tumor progression. VETC is a noncapillary network of HCC vessels that is prone to open into larger ones, as to deliver metastatic tumor cell clusters …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This vascular phenotype can be detected with increasing frequency, from the earliest stages of HCC, and its assessment is easy and reliably reproducible even in small‐sized tissues such as liver biopsy. In advanced HCC, VETC has been recently suggested to act as a predictor of sorafenib benefit; however, our data support the assessment of the VETC phenotype also in nonadvanced and resectable HCC for the identification of HCC patients at high risk of a more rapid tumor progression. VETC is a noncapillary network of HCC vessels that is prone to open into larger ones, as to deliver metastatic tumor cell clusters …”
Section: Discussionsupporting
confidence: 56%
“…Although conducted in a limited HCC population (hepatitis B virus [HBV]‐related and >5 cm), the authors elegantly showed VETC clusters delivering tumor emboli into larger vessels. Moreover, the same authors recently claimed sorafenib therapy to be more effective in VETC HCC …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Dingand and colleagues revealed that the sinusoidal-like vascular patterns were associated with a low overall survival rate and high early recurrence rate (70). Additionally, Fang et al unprecedentedly used threedimensional reconstruction to confirm that sinus vessels formed an interconnected network around a single HCC nodule, while capillaries showed discrete and disorganized patterns (71,72). They suggested that this vascular pattern was an effective mode of HCC metastasis independent of epithelial-to-mesenchymal transition.…”
Section: Vascular Patterns That Influence Mvdmentioning
confidence: 99%
“…Moreover, the VETC pattern may act as predictor of sorafenib bene t in patients with HCC, especially those with VETC. VETC can be an indicator for guiding the treatment of patients with recurrent HCC [21]. However, there are no studies regarding the prognostic value of the VETC pattern in recurrent early-stage HCC.…”
Section: Introductionmentioning
confidence: 99%